2011
DOI: 10.1515/rns.2011.055
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging for drug addiction and related behaviors

Abstract: In this review, we highlight the role of neuroimaging techniques in studying the emotional and cognitive-behavioral components of the addiction syndrome by focusing on the neural substrates subserving them. The phenomenology of drug addiction can be characterized by a recurrent pattern of subjective experiences that includes drug intoxication, craving, bingeing, and withdrawal with the cycle culminating in a persistent preoccupation with obtaining, consuming, and recovering from the drug. In the past two decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 236 publications
(266 reference statements)
1
80
1
4
Order By: Relevance
“…The alpha frequency has often been associated with addiction (see Parvas, Alia-Klein, Woicik, Volkow & Goldstein, 2011), including findings of increased alpha activity during withdrawal from both heroin (Shufman et al, 1996) and cocaine (Alper, Chabot, Kim, Prichep & John, 1990). The exact functional nature of alpha frequency in these processes is uncertain; for example Reid, Flammino, Howard, Nilsen and Prichep (2008) report findings that suggest increased frontal cortical alpha power to be positively associated with cocaine-induced nervousness, but frontal cortical alpha coherence to be negatively associated with cue-induced cocaine-like high.…”
Section: Discussionmentioning
confidence: 99%
“…The alpha frequency has often been associated with addiction (see Parvas, Alia-Klein, Woicik, Volkow & Goldstein, 2011), including findings of increased alpha activity during withdrawal from both heroin (Shufman et al, 1996) and cocaine (Alper, Chabot, Kim, Prichep & John, 1990). The exact functional nature of alpha frequency in these processes is uncertain; for example Reid, Flammino, Howard, Nilsen and Prichep (2008) report findings that suggest increased frontal cortical alpha power to be positively associated with cocaine-induced nervousness, but frontal cortical alpha coherence to be negatively associated with cue-induced cocaine-like high.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Tammela et al (2010) reported that EEG activity in the beta range throughout food picture presentation is related to disinhibition in obese women with binge eating disorder. Excess EEG high beta activity has also been shown with respect to drug-induced stressful states of craving (for a review see: Parvaz et al 2011) which are described as comparable to states of food craving preceding overeating episodes Styn et al 2013). Therefore, high beta frequencies are target to inhibition in the reduction of stressful arousal in several neurofeedback protocols Gruzelier 2001, 2004;Paquette et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Functional neuroimaging is often used to assess the effectiveness of addiction treatments, given the strong evidence for neurological alterations at the basis of drug dependence (e.g., Parvaz, Alia-Klein, Woicik, Volkow, & Goldstein, 2011;Volkow, Wang, Fowler, & Tomasi, 2012). Functional neuroimaging provides an objective and quantifiable measure for evaluating changes with treatment beyond what can be gathered from self-report or behavior alone (Menossi et al, 2013).…”
Section: Treatment Of Methamphetamine Use Disordersmentioning
confidence: 99%